STEM-based sound wave e-learning for high school students collaboration skills - Hidayah, Rizki Nur; Wiyono, Ketang; Ismet (AIP conference proceedings, 2024)
This study aims to produce a feasible and acceptable STEM-based sound wave e-learning to improve the student’s collaboration skills. This research consists of the planning, design, and development stages. The subject of this study were 30 students from the XI class of SMAN 2 Palembang. The instruments used in this study were feasibility instruments and student response questionnaires. Based on the needs analysis at the planning stage, it was found that 92.9% of respondents prefer to use cell phones as a medium in their daily lives. All students used google classroom and WhatsApp applications as learning media, and 100% of students feel that there needs to be a development of STEM-based e-learning to be used in physics learning. At the design stage, flowcharts and storyboards were made as a reference in the process of developing STEM-based sound wave e-learning. The development stage is carried out with the first prototyping, alpha test, and beta test. The results of the 2nd alpha test obtained 100 % of the feasibility percentage. Beta test results obtained 100 % of the acceptable percentage. Based on these studies, STEM-based sound wave e-learning has been feasible and acceptable to users, so it is suitable for use in physics learning in high school to improve students’ collaboration skills.